National Musical Heritage - the Influence of Michał Kleofas Ogiński’s Piano Songs on the Creativeness of Polish Romantic Composers - Gumper, Małgorzata (Sensus Historiae, 2020)
The article proposes to look at Prince Michał Kleofas Ogiński from an unpopular perspective which takes into account his participation in the formation of the national school in romantic music. The goal is to bring to the fore the magnate’s relationship with Polish culture of the 19th century, which has been marginalized so far due to his political functions. Another reason for ignoring the entire cultural contribution is to attach importance only to the popular polonaise Farewell to the Fatherland. After a short biography, the family and Józef Kozłowski’s contribution to education and cultivating Ogiński’s musical passions was presented. Then, the influence of Ogiński’s art on early works of Fryderyk Chopin, as well as its connections to Karol Kurpiński, Feliks Ostrowski, and the activities of Józef Elsner were presented. An important thread of his art is shown in Ogiński’s relationship with Maria Szymanowska, and in how his specific dace-march influenced the poetry of the Polish bard, Adam Mickiewicz. The links between Ogiński’s art and the development of vocal romances and the theater stage were also detailed. The whole ends with the analysis of short fragments of Letters about music, which concern the dramatic change in the sense of the magnate’s national identity during the partitions.